2012
DOI: 10.1038/pr.2012.159
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NO synthases and redox enzymes in umbilical arteries from newborns born small, appropriate, and large for gestational age

Abstract: Background: Modified expression of nitric oxide synthases (NOss) and an imbalance between the pro-oxidative and the antioxidative system accompany endothelial dysfunction, the first stage of atherosclerosis. humans born small (sGa) or large (LGa) for gestational age are at higher risk of developing atherosclerosis later in life than humans born appropriate for gestational age (aGa). We hypothesized that indicators of endothelial dysfunction could be detectable at birth. The purpose of this study was to find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…31,81 However, these results are controversial because they could not be replicated. 82 Moreover, differences in eNOS expression have been observed in human endothelial cells isolated from the umbilical arteries (HUAECs) or veins (HUVECs) of IUGR newborns. eNOS expression is increased in IUGR-HUAECs but decreased in IUGR-HUVECs.…”
Section: Impaired Enos Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…31,81 However, these results are controversial because they could not be replicated. 82 Moreover, differences in eNOS expression have been observed in human endothelial cells isolated from the umbilical arteries (HUAECs) or veins (HUVECs) of IUGR newborns. eNOS expression is increased in IUGR-HUAECs but decreased in IUGR-HUVECs.…”
Section: Impaired Enos Functionalitymentioning
confidence: 99%
“…In humans, independent studies have indicated that eNOS expression is increased in the umbilical arteries of babies born after fetal growth restriction, suggesting that activated NO synthesis may be a compensatory mechanism to improve placental blood flow 31 81 However, these results are controversial because they could not be replicated 82 . Moreover, differences in eNOS expression have been observed in human endothelial cells isolated from the umbilical arteries (HUAECs) or veins (HUVECs) of IUGR newborns.…”
Section: Mechanisms Involved In Endothelial Dysfunction In Individualmentioning
confidence: 99%
“…In this context, we found that eNOS expression is increased in endothelial cells of LGA of obese woman, suggesting a compensatory mechanism to maintain normal NO; however, eNOS activity is not different to control. There are few studies looking at eNOS expression in fetal endothelium of LGA, Dellee, Tobias, Li, and Mildenberger () found no differences in eNOS between LGA and AGA; however, they did not consider maternal BMI. This indicates that MO could increase eNOS protein expression in LGA newborns.…”
Section: Discussionmentioning
confidence: 99%